Prospects for the development of the cultural route Jewish heritage of Novi Sad as an element of the tourist offer - Mijuk Nenad (Turističko Poslovanje)
The focus of this research is on the development of the cultural route "Jewish Heritage of Novi Sad" as a potential segment of the city's tourist offer. Novi Sad, with its rich history of the Jewish community, represents an important cultural center whose heritage has shaped the social, cultural, and economic life of the region. This paper explores the possibilities of directing tourism toward Jewish cultural heritage, analyzes key aspects that make this segment attractive to tourists, and identifies the potentials and challenges in its development. Special emphasis is placed on the analysis of cultural and historical sites. Furthermore, the study examines ways of integrating Jewish heritage into the broader tourist offerings of the city, including education and guided tours. The goal is to determine how the development of this cultural route can contribute to the preservation of cultural identity, enhancement of the tourist offer, and the creation of new opportunities for the economic growth of Novi Sad.